Pharmacological and electrophysiological characterization of the human bile acid-sensitive ion channel (hBASIC) - Lefevre, Catherine M. T.; Diakov, Alexei; Härteis, Silke; Korbmacher, Christoph; Gruender, Stefan; Wiemuth, Dominik (Pflügers Archiv: European Journal of Physiology, 2014)
The human bile acid-sensitive ion channel (hBASIC) is a cation channel of the degenerin/epithelial Na(+) channel gene family that is expressed in the intestinal tract and can be activated by bile acids. Here, we show that in addition to its sensitivity for bile acids, hBASIC shares further key features with its rat ortholog: it is blocked by extracellular divalent cations, is inhibited by micromolar concentrations of the diarylamidine diminazene, and activated by millimolar concentrations of flufenamic acid. Furthermore, we demonstrate that two major bile acids present in human bile, chenodeoxycholic acid and deoxycholic acid, activate hBASIC in a synergistic manner. In addition, we determined the single-channel properties of hBASIC in outside-out patch clamp recordings, revealing a single-channel conductance of about 11 pS and a high Na(+) selectivity. Deoxycholic acid activates hBASIC in patch clamp recordings mainly by reducing the single-channel closed time. In summary, we provide a thorough functional characterization of hBASIC.
EVALuna2:4491